2021
DOI: 10.3390/children8100831
|View full text |Cite
|
Sign up to set email alerts
|

Parents and Peers in Child and Adolescent Development: Preface to the Special Issue on Additive, Multiplicative, and Transactional Mechanisms

Abstract: Parents and peers play critical roles in the socialization of children and adolescents, yet investigations on the role played by parents vs. peers have been largely separate for many years. To address this problem, we invited leading scholars in the field to collectively tell a complex story of the part that parents and peers together play in the development of children and adolescents. The resulting Special Issue is a collection of papers highlighting current conceptualizations and empirical work in this area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…A positive surrounding environment can arouse children's enthusiasm for learning. In line with the results of Harrist & Criss (2021), the family environment and peer environment have a significant role in the development of children and adolescents. As candidates for the nation's next generation, students must receive a quality education, even in less-than-optimal conditions.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…A positive surrounding environment can arouse children's enthusiasm for learning. In line with the results of Harrist & Criss (2021), the family environment and peer environment have a significant role in the development of children and adolescents. As candidates for the nation's next generation, students must receive a quality education, even in less-than-optimal conditions.…”
Section: Discussionmentioning
confidence: 52%
“…Chang et al (2018) showed that parental and peer support were directly and indirectly related to depression levels. Harrist & Criss (2021) concluded that the family environment and peer environment have a significant role in the development of children and adolescents. Suldo et al (2008) research corroborates that students who can communicate and rely on family members have fewer mental health problems.…”
Section: Introductionmentioning
confidence: 99%
“…A youth's social context is critically important to healthy development and desistance from crime. Although an individual's social context spans many social interactions across levels, parents and peers are adolescents' two primary agents of socialization (Harrist & Criss, 2021).…”
Section: Developmentally Supported Alternatives For Policy and Practicementioning
confidence: 99%
“…ver the past few decades, interest and attention toward the rapid and significant physical, psychological, emotional, and social changes in adolescents have been increasing daily. During the developmental period of adolescence, individuals possess the highest and fastest growth potential and, if given the necessary and sufficient conditions for growth, will achieve their highest excellence (Harrist & Criss, 2021). As mentioned, during this period, individuals experience multiple comprehensive changes due to the maturation process, which can potentially impact the adolescent's life.…”
Section: Introductionmentioning
confidence: 99%